An Estimate of the Effect of Common Currencies on Trade and Income - Frankel, J.; Rose, A. (Quarterly Journal of Economics, 2002)
To quantify the implications of common currencies for trade and income, we use data for over 200 countries and dependencies. In our two-stage approach, estimates at the first stage suggest that belonging to a currency union/board triples trade with other currency union members. Moreover, there is no evidence of trade-diversion. Our estimates at the second stage suggest that every one percent increase in a country’s overall trade (relative to GDP) raises income per capita by at least one third of a percent. We combine the two estimates to quantify the effect of common currencies on output. Our results support the hypothesis that important beneficial effects of currency unions come through the promotion of trade.